Toksitas Ekstrak Metanol Kulit Jengkol (Pithecellobium Jiringa) dengan Metode Brine Shrimp Lethality Test Terhadap Larva udang (Artemia salina) - Alfin Surya (Universitas Putera Batam, 2018)
Methanol extract Jengkol Skin (Pithecellobium jiringa) contains Flavonoid compounds that are thought to have potential as anticancer. This study aims to determine the activity of jengkol skin toxicity with maceration for 72 hours against shrimp larvae (Artemia salina) using Brine Shrimp Lethality Test (BSLT) method which has correlation in source of new anticancer compound, resulting in Median Lethal Concentration (LC50 ) for methanol solvent is 126 ppm.